Coil component and method for manufacturing a coil component

JP7943876B2Active Publication Date: 2026-10-30TAIYO YUDEN KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024035668
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2026-10-30
Estimated Expiration
2039-10-24

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、絶縁の信頼性の向上を図ることが可能なコイル部品が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943876000003
    Figure 0007943876000003
  • Figure 0007943876000004
    Figure 0007943876000004
  • Figure 0007943876000005
    Figure 0007943876000005
Patent Text Reader

Abstract

To provide a coil component that achieves both insulation reliability and downsizing, and a method for manufacturing the same.SOLUTION: The coil component comprises: a substrate 10 that contains a metal magnetic particle 31 having a first average grain diameter and a ceramic particle 32 having a second average grain diameter that is smaller than the first average grain diameter; and a coil conductor that is disposed in the substrate and that includes a first conductor part and a second conductor part that is disposed in the substrate so as to face the first conductor part. In an inter-conductor region of the substrate that exists between the first and second conductor parts, the volume ratio of the ceramic particle to the total volume of the metal magnetic and ceramic particles is 3 vol% or greater, and the content of the metal magnetic particle in a region other than the inter-conductor region of the substrate is larger than the content of the metal magnetic particle in the inter-conductor region.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to a coil component and a method for manufacturing the coil component.

Background Art

[0002] Various magnetic materials have been conventionally used as materials for magnetic bases of electronic components. For example, ferrite is often used as a magnetic material for coil components such as inductors. Ferrite has high magnetic permeability, so it is suitable as a magnetic material for the base of coil components.

[0003] As magnetic materials for electronic components other than ferrite, metal magnetic materials containing metal magnetic particles are known. Since metal magnetic materials have higher saturation magnetic flux density than ferrite, they are suitable as materials for magnetic bases of coil components through which large currents flow.

[0004] An insulating film is provided on the surface of each metal magnetic particle contained in the magnetic base to prevent short circuits from occurring between adjacent metal magnetic particles. However, the magnetic base made of a metal magnetic material has a problem that its volume resistivity is lower than that of a magnetic base made of ferrite, and dielectric breakdown is likely to occur. Japanese Patent Laid-Open No. 2017-092431 discloses a coil component in which three or more metal magnetic particles are arranged between internal conductors to improve insulation in the region between the internal conductors of the magnetic base.

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0006] Coil components require not only high insulation reliability but also miniaturization. Increasing the spacing between opposing parts of the internal conductors improves insulation reliability, but it also increases the dimensions in the thickness direction.

[0007] One of the objectives of the present invention is to provide a coil component that can be miniaturized while ensuring insulation reliability between internal conductors, and a method for manufacturing such a coil component. Other objectives of the present invention will be revealed throughout the specification. [Means for solving the problem]

[0008] A coil component according to one embodiment of the present invention comprises a substrate containing metallic magnetic particles having a first average particle size and ceramic particles having a second average particle size smaller than the first average particle size, and a coil conductor provided within the substrate and including a first conductor portion and a second conductor portion provided within the substrate so as to face the first conductor portion. In one embodiment, in the interconductor region of the substrate between the first conductor portion and the second conductor portion, the volume ratio of the ceramic particles to the total volume of the metallic magnetic particles and the ceramic particles is 3 vol% or more.

[0009] In one embodiment of the present invention, the content ratio of the ceramic particles to the metal magnetic particles in the interconductor region is 15 vol% or less.

[0010] In one embodiment of the present invention, the first conductor portion and the second conductor portion are made of a conductive material containing a metal, and the substrate substantially does not contain atoms of the metal in the interconductor region.

[0011] In one embodiment of the present invention, the ceramic particles consist of silica, alumina, zirconia, or titania.

[0012] In one embodiment of the present invention, the second average particle size is 1 / 50 or less of the first average particle size. In another embodiment of the present invention, the second average particle size is 1 / 200 or more of the first average particle size.

[0013] One embodiment of the present invention relates to a circuit board comprising the above-mentioned coil component. One embodiment of the present invention relates to an electronic component comprising the above-described circuit board.

[0014] A method for manufacturing a coil component according to one embodiment of the present invention comprises the steps of: preparing a molded body containing metallic magnetic particles having a first average particle size and ceramic particles having a second average particle size smaller than the first average particle size, with a coil conductor disposed inside; and heating the molded body at a temperature lower than the melting temperature of the ceramic particles. In one embodiment, the volume ratio of the ceramic particles to the total volume of the metallic magnetic particles and the ceramic particles is 3 vol% or more. [Effects of the Invention]

[0015] According to the present invention, a coil component is provided that can improve the reliability of insulation. [Brief explanation of the drawing]

[0016] [Figure 1] This is a perspective view of a coil component relating to one embodiment of the present invention. [Figure 2] Figure 1 is an exploded perspective view of the coil component. [Figure 3] This is a schematic cross-sectional view showing the cross-section along line XX in Figure 1. [Figure 4] This is an enlarged cross-sectional view schematically showing region A in Figure 3. [Modes for carrying out the invention]

[0017] Various embodiments of the present invention will be described below with reference to the drawings as appropriate. Note that components common to multiple drawings are denoted by the same reference numerals throughout the drawings. It should be noted that, for the sake of clarity, the drawings are not necessarily drawn to an exact scale.

[0018] With reference to FIG. 1 to FIG. 4, a coil component 1 according to an embodiment of the present invention will be described. The coil component 1 is an example of a coil component to which the present invention is applied. In the illustrated embodiment, the coil component 1 is a multilayer inductor. This multilayer inductor can be used as a power inductor incorporated in a power supply line and various other inductors. The present invention can be applied to various coil components other than the illustrated multilayer inductor.

[0019] As illustrated, the coil component 1 includes a base 10, a coil conductor 25 provided inside the base 10, an external electrode 21 provided on the surface of the base 10, and an external electrode 22 provided at a position spaced apart from the external electrode 21 on the surface of the base 10.

[0020] The coil component 1 is mounted on a circuit board 2. The circuit board 2 is provided with two land portions 3a and 3b. The coil component 1 may be mounted on the circuit board 2 by joining each of the external electrodes 21, 22 to the corresponding land portion 3 of the circuit board 2 with solder. The circuit board 2 can include the coil component 1 and various electronic components other than the coil component 1. The circuit board 2 can be mounted in various electronic devices. Electronic devices in which the circuit board 2 can be mounted include smartphones, tablets, game consoles, electronic devices used for automotive electrical components, and various other electronic devices. The application of the coil component 1 is not limited to those explicitly specified in the present specification.

[0021] The base body 10 is formed in a generally rectangular parallelepiped shape. The base body 10 has a first main surface 10a, a second main surface 10b, a first end surface 10c, a second end surface 10d, a first side surface 10e, and a second side surface 10f. The outer surface of the main body 10 is defined by these six surfaces. The first main surface 10a and the second main surface 10b face each other, the first end surface 10c and the second end surface 10d face each other, and the first side surface 10e and the second side surface 10f face each other. In FIG. 1, since the first main surface 10a is located on the upper side of the main body 10, the first main surface 10a may be referred to as the "upper surface". Similarly, the second main surface 10b may be referred to as the "lower surface". Since the magnetically coupled coil component 1 is arranged such that the second main surface 10b faces the circuit board 2, the second main surface 10b may also be referred to as the "mounting surface". When referring to the vertical direction of the magnetically coupled coil component 1, the vertical direction in FIG. 1 is used as a reference. In this specification, unless otherwise understood from the context, the "length" direction, "width" direction, and "thickness" direction of the coil component 1 are respectively the "L-axis" direction, "W-axis" direction, and "T-axis" direction in FIG. 1. The L-axis, W-axis, and T-axis are orthogonal to each other. The coil axis Y extends along the T direction. The coil axis Y, for example, passes through the intersection of the diagonals of the first main surface 10a having a rectangular shape in plan view and extends in a direction perpendicular to the first main surface 10a.

[0022] In one embodiment of the present invention, the coil component 1 is formed such that the length dimension (dimension in the L-axis direction) is 0.2 to 6.0 mm, the width dimension (dimension in the W-axis direction) is 0.1 to 4.5 mm, and the thickness dimension (dimension in the T-axis direction) is 0.1 to 4.0 mm. These dimensions are merely examples, and the coil component 1 to which the present invention can be applied may take any dimensions as long as they do not contradict the gist of the present invention. In one embodiment, the coil component 1 is formed with a low profile. For example, the coil component 1 is formed such that its width dimension is larger than its thickness dimension.

[0023] As shown in Figures 2 and 3, the substrate 10 has multiple stacked magnetic layers. As shown in the figures, the substrate 10 comprises a main body 20, an upper cover layer 18 provided on the upper surface of the main body 20, and a lower cover layer 19 provided on the lower surface of the main body 20. The main body 20 includes stacked magnetic layers 11 to 16. In the substrate 10, the layers are stacked in the following order from top to bottom in Figure 2: upper cover layer 18, magnetic layer 11, magnetic layer 12, magnetic layer 13, magnetic layer 14, magnetic layer 15, magnetic layer 16, magnetic layer 17, and lower cover layer 19.

[0024] The upper cover layer 18 includes four magnetic layers 18a to 18d. In this upper cover layer 18, the magnetic layers 18a, 18b, 18c, and 18d are stacked in that order from bottom to top as shown in Figure 2.

[0025] The lower cover layer 19 includes four magnetic layers 19a to 19d. In this lower cover layer 19, the magnetic layers 19a, 19b, 19c, and 19d are stacked in that order from top to bottom in Figure 2.

[0026] Each of the magnetic layers 11 to 16 is provided with a corresponding conductor pattern C11 to C16. These conductor patterns C11 to C16 constitute a coil conductor 25. This coil conductor 25 has a coil axis Y. Each conductor pattern C11 to C16 is formed to extend around the coil axis Y. In the illustrated embodiment, the coil axis Y extends in the T-axis direction and coincides with the stacking direction of the magnetic layers 11 to 16.

[0027] In another embodiment of the present invention, the magnetic layers 11 to 16 may be stacked in the L-axis direction. In this case, by forming conductor patterns C11 to C16 on the surfaces of the magnetic layers 11 to 16, the coil axis Y is oriented in the same L-axis direction as the stacking direction of the magnetic layers 11 to 16. In another embodiment of the present invention, the magnetic layers 11 to 16 may be stacked in the W-axis direction. In this case, by forming conductor patterns C11 to C16 on the surfaces of the magnetic layers 11 to 16, the coil axis Y is oriented in the same W-axis direction as the stacking direction of the magnetic layers 11 to 16.

[0028] Coil component 1 may include any number of insulating layers in addition to insulating layers 11 to 16, insulating layers 18a to 18d, and insulating layers 19a to 19d, as needed. Some of insulating layers 11 to 16, insulating layers 18a to 18d, and insulating layers 19a to 19d may be omitted as appropriate. In Figure 3, the boundaries between magnetic material layers are shown, but in the actual substrate of a coil component to which the present invention is applied, the boundaries between magnetic material layers may not be visible.

[0029] Conductor patterns C11 to C16 are formed on the corresponding insulating layers 11 to 16, respectively. Conductor patterns C11 to C16 are formed using printing such as screen printing, plating, etching, or any other known method. Vias V1 to V5 are formed at predetermined positions in insulating layers 11 to 15, respectively. Vias V1 to V5 are formed by creating through holes that penetrate insulating layers 11 to 15 in the T-axis direction at predetermined positions in insulating layers 11 to 15, and filling these through holes with conductive material. Conductor patterns C11 to C16 and vias V1 to V5 contain metals with excellent conductivity, such as Ag, Pd, Cu, Al, or alloys thereof.

[0030] In this specification, the region of the substrate 10 located between adjacent conductor patterns C11 to C16 is referred to as the interconductor region. In other words, the interconductor region is a part of the substrate 10, and is the region sandwiched between adjacent conductor patterns. Figure 3 shows five interconductor regions 10X. One of the interconductor regions 10X is located between conductor pattern C11 and conductor pattern C12 adjacent to that adjacent pattern C11. The other interconductor regions 10X are also located between adjacent conductor patterns as shown in the figure.

[0031] The interconductor region 10X will be further explained with reference to Figure 4. Figure 4 shows an enlarged view of region A in Figure 3. Region A includes a part of the conductor pattern C12, a part of the conductor pattern C13, and a part of the interconductor region 10X located between the conductor patterns C12 and C13. As shown in the figure, the substrate 10 contains a plurality of metallic magnetic particles 31 and a plurality of ceramic particles 32 in the interconductor region 10X.

[0032] The metallic magnetic particles 31 are particles or powders made of a soft magnetic metallic material. Examples of soft magnetic metallic materials for the metallic magnetic particles 31 are particles of (1) metallic Fe or Ni, (2) alloy Fe-Si-Cr, Fe-Si-Al or Fe-Ni, (3) amorphous Fe-Si-Cr-BC or Fe-Si-B-Cr, or (4) mixtures thereof.

[0033] The average particle size of the metallic magnetic particles 31 is, for example, 2 μm to 10 μm. The average particle size of the metallic magnetic particles 31 is not limited to the range of 2 μm to 10 μm and can be changed as appropriate. In this specification, "average particle size" of magnetic particles means volume-based average particle size unless otherwise specified. The volume-based average particle size of magnetic particles is measured by laser diffraction scattering in accordance with JIS Z 8825. As a laser diffraction / scattering device, for example, a laser diffraction / scattering particle size distribution analyzer (model number: LA-960) manufactured by Horiba, Ltd. in Kyoto City, Kyoto Prefecture, Japan can be used.

[0034] The metallic magnetic particles 31 may contain two types of metallic magnetic particles with different average particle sizes. When the metallic magnetic particles 31 contain two types of metallic magnetic particles with different average particle sizes, the larger average particle size of the metallic magnetic particles 31 may be, for example, 2 μm to 10 μm, and the smaller average particle size of the metallic magnetic particles 31 may be, for example, 1 / 20 to 1 / 2 of the larger average particle size. The smaller average particle size of the metallic magnetic particles 31 with different average particle sizes may be, for example, 0.2 μm to 1 μm. The metallic magnetic particles 31 may contain three or more types of metallic magnetic particles having different average particle sizes.

[0035] An insulating film is provided on the surface of the metallic magnetic particles 31. The insulating film on the surface of the metallic magnetic particles 31 may be, for example, an oxide film formed by the oxidation of the surface of the metallic magnetic particles 31. An insulating coating film may be provided on the surface of the metallic magnetic particles 31. This coating film may be, for example, made of silica or a thin film containing silica.

[0036] The ceramic particles 32 are particles or powders made of a ceramic material having a smaller average particle size than the metal magnetic particles 31. The ceramic particles 32 are made of a ceramic material having a higher electrical resistivity than the metal magnetic particles 31. For example, the ceramic particles 32 are particles made of silica, alumina, zirconia, or titania, or mixed particles made of these materials. The ceramic particles 32 have higher insulating properties than the metal magnetic particles 31 provided with an insulating film.

[0037] The average particle size of the ceramic particles 32 is, for example, 10 to 50 nm. The average particle size of the ceramic particles 32 may be 1 / 50 or less of the average particle size of the metal magnetic particles 31. The average particle size of the ceramic particles 32 may be 1 / 100 or less of the average particle size of the metal magnetic particles 31. In one embodiment, the average particle size of the ceramic particles 32 may be 1 / 200 or more of the average particle size of the metal magnetic particles 31. The average particle size of the ceramic particles 32 may be 1 / 50 or less and 1 / 200 or more of the average particle size of the metal magnetic particles 31. If the metal magnetic particles 31 include two or more types of metal magnetic particles with different average particle sizes, the average particle size of the ceramic particles 32 is compared with the average particle size of the largest of the multiple types of metal magnetic particles 31. That is, the average particle size of the ceramic particles 32 may be 1 / 50 or less of the average particle size of the largest of the multiple types of metal magnetic particles 31.

[0038] In one embodiment of the present invention, in the interconductor region 10X of the substrate 10, the content of ceramic particles 32 relative to the total volume of metal magnetic particles 31 and ceramic particles 32 is 3 vol% or more in terms of volume ratio. In another embodiment of the present invention, in the interconductor region 10X of the substrate 10, the content of ceramic particles 32 relative to the total volume of metal magnetic particles 31 and ceramic particles 32 is 15 vol% or less in terms of volume ratio.

[0039] The volume of the metallic magnetic particles 31 contained in the substrate 10 is obtained by measuring the particle size of each metallic magnetic particle appearing in a cross-section obtained by cutting the substrate 10, using the laser diffraction scattering method in accordance with JIS Z 8825, and then converting the resulting particle size into volume. When converting from particle size to volume, it is assumed that each magnetic particle is spherical, in light of the measurement principle of the laser diffraction scattering method in accordance with JIS Z 8825. The volume of the ceramic particles 32 is also measured and calculated in the same way as the volume of the metallic magnetic particles 31.

[0040] In one embodiment of the present invention, the interconductor region 10X is substantially free of metal atoms contained in the coil conductor 25. For example, if the conductor patterns C11 to C16 contain a certain metal (e.g., Ag), it can be determined that the interconductor region 10X is substantially free of metal atoms contained in the coil conductor 25 if the amount of that metal element contained in the interconductor region 10X is 1% or less of the amount of that metal element contained in a predetermined region within the conductor patterns C11 to C16. More specifically, the coil component 1 is cut along its thickness direction (T direction) to expose a cross-section including at least one of the conductor patterns C11 to C16 and the interconductor region 10X, and energy-dispersive X-ray analysis (EDS) is performed on the region of the cross-section containing the conductor patterns C11 to C16 and the region containing the interconductor region 10X to compare the amount of that metal element contained in the conductor patterns C11 to C16 and the amount of that metal element contained in the interconductor region 10X. For example, if the conductor patterns C11 to C16 contain Ag, the elemental amounts of Ag in a 1 μm square region A1 within the conductor pattern C12 and a 1 μm square region A2 within the interconductor region 10X, as shown in Figure 4, can be analyzed by EDS. If the count value of the detected Ag peak obtained in region A2 is 1 / 100 or less of the count value of the detected Ag peak obtained in region A1, then it can be determined that there are substantially no atoms of the metal contained in the conductor patterns C11 to C16 (i.e., the metal contained in the coil conductor 25) in the interconductor region 10X. In conventional coil components, the substrate does not contain ceramic particles corresponding to the ceramic particles 32 in the above embodiment, so metal atoms contained in the conductor pattern diffuse into the interconductor region. For this reason, in conventional coil components, metal atoms contained in the coil conductor (conductor pattern) are present in the interconductor region of the substrate. In contrast, in the embodiment of the present invention, since the interconductor region 10X contains 3 vol% or more of ceramic particles 32, metal atoms do not diffuse from the conductor patterns C11 to C16 into the interconductor region 10X. As a result, the interconductor region 10X is substantially free of metal atoms contained in the conductor patterns C11 to C16.Therefore, the physical properties of the interconductor region 10X of the substrate 10 are not affected by the metal atoms contained in the conductor patterns C11-C16 (for example, by the diffusion of these metal atoms into the interconductor region 10X). For example, the dielectric strength in the interconductor region 10X is not affected by the metal atoms contained in the conductor patterns C11-C16. In other words, the metal atoms contained in the conductor patterns C11-C16 do not substantially reduce the insulation resistance value of the interconductor region 10X.

[0041] The substrate 10 may contain a binder to strengthen the bonding between the metal magnetic particles 31. The binder included in the substrate 10 may be a thermosetting resin with excellent insulating properties, such as epoxy resin, phenolic resin, polyimide resin, silicone resin, polystyrene (PS) resin, high-density polyethylene (HDPE) resin, polyoxymethylene (POM) resin, polycarbonate (PC) resin, polyvinyldenine fluoride (PVDF) resin, phenolic resin, polytetrafluoroethylene (PTFE) resin, polybenzoxazole (PBO) resin, polyvinyl alcohol (PVA) resin, polyvinyl butyral (PVB) resin, or acrylic resin.

[0042] The substrate 10 may also contain metallic magnetic particles 31 and ceramic particles 32 in regions other than the interconductor region 10X. The content of ceramic particles 32 in regions of the substrate 10 other than the interconductor region 10X may be less than the content of ceramic particles 32 in the interconductor region 10X. For example, in the core region of the substrate 10 located inside the coil conductor 25 in the radial direction centered on the Y axis, the content of ceramic particles 32 can be reduced compared to the content in the interconductor region 10X. This allows for a higher content of metallic magnetic particles 31 in the core region, thereby improving the effective permeability of the coil component 1.

[0043] Next, an example of a method for manufacturing the coil component 1 will be described. In one embodiment of the present invention, the coil component 1 is manufactured by a sheet manufacturing method using a magnetic sheet. When manufacturing the coil component 1 by the sheet manufacturing method, first, an upper laminate which will become the upper cover layer 18, an intermediate laminate, and a lower laminate which will become the lower cover layer 19 are formed. The upper laminate is formed by laminating a plurality of magnetic sheets which will become the magnetic layers 18a to 18d, the lower laminate is formed by laminating a plurality of magnetic sheets which will become the magnetic layers 19a to 19d, and the intermediate laminate is formed by laminating a plurality of magnetic sheets which will become the magnetic layers 11 to 16. The magnetic sheet is manufactured by, for example, kneading a group of particles including metallic magnetic particles 31 and ceramic particles 32 with a resin, placing the resulting slurry into a molding die, and applying a predetermined molding pressure. As the resin kneaded with the metallic magnetic particles 31 and ceramic particles 32, for example, a resin material with excellent insulating properties such as polyvinyl butyral (PVB) resin or epoxy resin can be used.

[0044] The intermediate laminate is formed by stacking multiple magnetic sheets, each having a conductor pattern corresponding to conductor patterns C11 to C16. Through holes are formed in each of the magnetic sheets for the intermediate laminate, penetrating in the stacking direction. Conductor patterns corresponding to conductor patterns C11 to C16 are formed on these through holes in the magnetic sheets by screen printing or the like. At this time, the metal material constituting each conductor pattern is embedded in the through holes of the magnetic sheets, forming vias. After forming each sheet containing each conductor pattern C11 to C16, the base film is removed, and the intermediate laminate is obtained by stacking them sequentially, starting with the sheet containing conductor pattern C16 and continuing down to the sheet containing conductor pattern C11.

[0045] Next, the intermediate laminate prepared as described above is sandwiched between the upper and lower laminates from above and below, and these upper and lower laminates are heat-pressed onto the intermediate laminate to obtain the main laminate. Then, the main laminate is cut into pieces of the desired size using a cutting machine such as a dicing machine or a laser processing machine to obtain a chip laminate.

[0046] Next, the chip laminate is degreased, and the degreased chip laminate is heat-treated. The heat treatment of the chip laminate is performed at a temperature lower than the melting point of the ceramic particles 32 contained in the chip laminate. The ceramic particles 32 melt at temperatures above 1000°C. If the ceramic particles 32 are silica, they melt at approximately 1500°C. The heat treatment of the chip laminate is performed, for example, at 400°C to 900°C for 20 to 120 minutes. The ceramic particles 32 are not oxidized or reduced during the heat treatment of the laminate. The material of the ceramic particles 32 is selected to not undergo oxidation or reduction reactions below 900°C.

[0047] Next, external electrodes 21 and 22 are formed by applying conductive paste to both ends of the heat-treated chip laminate. Through these steps, the coil component 1 is obtained.

[0048] The coil component 1 may be manufactured by a method known to those skilled in the art other than the sheet manufacturing method, such as the slurry build method or the thin-film process method. By manufacturing the coil component 1 by the slurry build method or the thin-film process method, it becomes easy to make the content of ceramic particles 32 in the interconductor region 10X of the substrate 10 different from the content of ceramic particles 32 in the core region of the substrate 10 located inside the coil conductor 25 in the radial direction centered on the Y axis. For example, by making the content of ceramic particles 32 in the core region of the substrate 10 less than the content of ceramic particles 32 in the interconductor region 10X, the content of metallic magnetic particles 31 in the core region can be increased, thereby improving the effective magnetic permeability of the coil component 1.

[0049] The illustrated multilayer inductor is an example of a coil component to which the present invention can be applied, and the present invention can be applied to various types of coil components other than multilayer inductors. For example, the present invention can also be applied to planar coils.

[0050] The coil component according to the present invention may be manufactured by a compression molding process instead of a lamination process. When manufacturing the coil component 1 by a compression molding process, first a slurry is created by kneading a group of particles including metallic magnetic particles 31 and ceramic particles 32 with a binder resin. Next, the slurry is placed in a molding die in which a coil conductor is installed, and molding pressure is applied to obtain a molded body containing the coil conductor. Next, a base body 10 is obtained by heat-treating the molded body at a temperature lower than the melting temperature of the ceramic particles 32. Next, external electrodes 21 and 22 are formed on the surface of the base body 10 by applying a conductive paste to the base body 10. In this way, the coil component 1 is manufactured by a compression molding process. [Examples]

[0051] Examples of the present invention will now be described. First, metallic magnetic particles having the composition Fe-Si-Cr (Fe: 92 wt%, Si: 3.5%, Cr: 4.5 wt%) were prepared. Next, these metallic magnetic particles and silica particles as ceramic particles were mixed in the ratios shown in Table 1 to obtain a mixed powder. Table 1 shows the volume ratios of the content of the metallic magnetic particles and ceramic particles in this mixed powder relative to the total volume of the metallic magnetic particles and ceramic particles. Next, this mixed powder was kneaded with polyvinyl butyral to prepare a slurry. Next, this slurry was formed into long sheets using a coating machine such as a die coater, and these sheets were cut to create multiple rectangular parallelepiped magnetic sheets with a thickness of 8 μm. In this way, multiple sheets of nine different types of magnetic sheets (nine magnetic sheets, from the first to the ninth magnetic sheet) with different ceramic particle content were prepared.

[0052] Next, through-holes were made in predetermined positions on the first magnetic sheet using a laser or the like. Then, a conductive paste containing Ag was embedded in the through-holes, and the conductive paste containing Ag was printed on the magnetic sheet in a predetermined pattern. The first magnetic sheets, on which the conductive patterns were formed in this way, were stacked so that the conductive patterns formed on different first magnetic sheets were electrically connected via the conductors embedded in the through-holes, and pre-pressed at 60°C to obtain a laminate. Laminates were similarly prepared using each of the second to ninth magnetic sheets. Next, each of these nine types of laminates was separated into individual pieces using a dicing machine. Next, these separated chip laminates were degreased, and the degreased chip laminates were subjected to a heat treatment at 800°C. External electrodes were formed on the evaluation chips after the heat treatment to obtain nine types of evaluation coil conductors (samples A1 to A9). The dimensions of these evaluation coil conductors in the L, W, and T directions were 1.6 mm, 0.8 mm, and 0.8 mm, respectively, and they contained a 4.5-turn coil conductor inside.

[0053] Twenty samples each of samples A1 to A9 were prepared, and a deflection test was performed on each of the evaluation coil conductors of samples A1 to A9. The deflection test was carried out as follows: First, the evaluation coil conductor was mounted on a glass epoxy substrate with a thickness of 0.8 mm. The substrate was then attached between a pair of support posts with a radius of 2.5 mm, spaced 90 mm apart. The center of the underside of the substrate attached between the support posts was then pressed down to a depth of 10 mm at a speed of 2.5 mm / second using an indenter with a tip radius of curvature of R340, thereby deflecting the substrate. This deflection test was performed while monitoring the resistance of the evaluation coil. Among the evaluation coil conductors, those that showed no conduction failure and no visible cracks when the indenter was pressed down to a depth of 10 mm were considered good products.

[0054] Table 1 shows the results of the deflection test. As shown in Table 1, for samples A1 to A6, each containing 15 vol% or less of ceramic particles, no conduction failure or cracking occurred in any of the 20 evaluation coil components. Thus, it was found that even when the substrate of the coil conductor contains ceramic particles, the coil component has sufficient deflection strength if the content is 15 vol% or less. [Table 1]

[0055] As described above, increasing the content of ceramic particles 32 in the interconductor region 10X degrades the bending strength. If the content of ceramic particles 32 in the interconductor region 10X is further increased to, for example, 100 vol%, delamination is more likely to occur during the manufacturing process. This delamination during the manufacturing process is undesirable because it degrades the yield. In addition, when the content of ceramic particles 32 in the interconductor region 10X reaches 100 vol%, the inductance of the coil component deteriorates.

[0056] Next, multiple copies of nine types of magnetic sheets (first magnetic sheet to ninth magnetic sheet) were prepared in the same manner as the preparation process for samples A1 to A9. Then, a conductive paste containing Ag was printed on each of two first magnetic sheets in a predetermined pattern. These two first magnetic sheets with the printed conductive pattern were laminated so that the conductive patterns of each sheet faced each other. A predetermined number of first magnetic sheets without the conductive pattern printed on them were laminated on the top and bottom surfaces of these two first magnetic sheets, and a pre-press bond was performed at 60°C to obtain a laminate. Laminates were prepared similarly using each of the second magnetic sheet to ninth magnetic sheet. Next, each of these nine types of laminates was separated into individual pieces using a dicing machine. Next, these separated chip laminates were degreased, and the degreased chip laminates were subjected to a heat treatment at 800°C. External electrodes were formed on the evaluation chips after the heat treatment to obtain nine types of evaluation capacitor chips (samples B1 to B9). The dimensions of this evaluation capacitor chip in the L, W, and T directions are 1.6 mm × 0.8 mm × 0.8 mm, respectively.

[0057] Furthermore, for each of the evaluation capacitor chips B1 to B9, the voltage applied between the external electrodes was increased in stages, and the voltage at which a short circuit occurred was measured. The voltage at which the short circuit occurred, divided by the distance between the electrodes, was given as the withstand voltage for each sample, and this is summarized in Table 2. [Table 2]

[0058] As shown in Table 2, samples B3 to B9, which contained 3 vol% or more of ceramic particles, had a withstand voltage of 2.0 V / μm or higher. For power supply inductors where high current handling of coil components is desired, a withstand voltage of 2 V / μm or higher is desirable. As shown in Table 2, it was found that a substrate with a withstand voltage of 2 V / μm or higher can be obtained if the ceramic particle content is 3 vol% or higher. By using this substrate as the base for coil components, coil components with a withstand voltage of 2 V / μm or higher can be obtained.

[0059] Next, the effects of the above embodiment will be explained. In the above embodiment, the substrate 10 contains ceramic particles 32 that have higher insulating properties than the metallic magnetic particles 31 in the interconductor region 10X, so the volume resistivity of the substrate 10 in the interconductor region 10X can be improved. As a result, a coil component 1 with improved insulation resistance, i.e., withstand voltage, between the conductor patterns C11 to C16 can be obtained. In particular, when the content of ceramic particles 32 is 3 vol% or more, a coil component 1 with a high withstand voltage of 2 V / μm or more can be obtained.

[0060] According to the above embodiment, since the average particle size of the ceramic particles 32 is smaller than the average particle size of the metal magnetic particles 31, the ceramic particles 32 can enter the gaps between the metal magnetic particles 31. Therefore, even if ceramic particles 32 are added, the volume of the interconductor region 10X hardly increases. Thus, according to the above embodiment, the volume resistivity of the interconductor region 10X can be improved while suppressing an increase in the dimensions of the interconductor region 10X. By making the average particle size of the ceramic particles 32 1 / 50 or 1 / 100 or less of the average particle size of the metal magnetic particles 31, the ceramic particles 32 can easily enter the gaps between the metal magnetic particles 31. In this case, even if ceramic particles 32 are added, the dimensions of the interconductor region 10X do not substantially increase, so the volume resistivity can be improved without increasing the dimensions of the interconductor region 10X. If the average particle size of the ceramic particles 32 becomes smaller than 1 / 200 of the average particle size of the metal magnetic particles 31, the ceramic particles 32 will have difficulty entering the gaps between the metal magnetic particles 31 due to slurry aggregation, etc. Therefore, it is preferable that the average particle size of the ceramic particles 32 be 1 / 200 or more of the average particle size of the metal magnetic particles 31.

[0061] Conductor patterns C11-C16 contain metal. Some of this metal exists as cations in conductor patterns C11-C16. During the heat treatment in the manufacturing of coil component 1, the metal element (e.g., Fe) contained in the metal magnetic particles 31 is oxidized. When electrons released when the metal magnetic particles 31 are oxidized react with the cations (Ag+) of the metal (e.g., Ag) in conductor patterns C11-C16 in the interconductor region 10X, the metal (Ag) is deposited in the interconductor region 10X. In other words, the metal contained in conductor patterns C11-C16 can diffuse into the interconductor region 10X. According to the above embodiment, the presence of ceramic particles 32 in the interconductor region 10X reduces the contact area between conductor patterns C11-C16 and the metal magnetic particles 31 contained in the interconductor region 10X, making it difficult for metal atoms contained in conductor patterns C11-C16 to diffuse into the interconductor region 10X. In one embodiment, the metal atoms contained in the conductor patterns C11 to C16 are substantially absent in the interconductor region 10X. When the metal atoms contained in the conductor patterns C11 to C16 diffuse into the interconductor region 10X, it becomes a factor that degrades the insulation properties of the interconductor region 10X. However, according to the above embodiment, since the metal atoms contained in the conductor patterns C11 to C16 do not diffuse into the interconductor region 10X, the insulation resistance, i.e., the dielectric strength, of the interconductor region 10X can be further improved.

[0062] According to the above embodiment, in the interconductor region 10X of the substrate 10, the content of ceramic particles 32 relative to the total volume of metal magnetic particles 31 and ceramic particles 32 is set to 15 vol% or less in terms of volume ratio. Therefore, it is possible to improve the volume resistivity of the interconductor region 10X while suppressing the deterioration of the bending strength of the substrate 10 due to the addition of ceramic particles 32. The bending strength of the substrate 10 containing metal magnetic particles 31 is ensured by the bonding of the metal magnetic particles 31 within the substrate 10. By setting the content of ceramic particles 32 to 15 vol% or less, the bonding of the metal magnetic particles 31 is not inhibited, and as a result, a decrease in the bending strength of the substrate 10 can be prevented or suppressed.

[0063] According to the above embodiment, since the heating in the manufacturing process of the coil component 1 is performed at a temperature lower than the melting temperature of the ceramic particles 32, distortion of the shape of the substrate 10 due to the flow of the ceramic particles 32 can be prevented. This prevents a decrease in insulation resistance, i.e., a decrease in withstand voltage, due to a reduction in the spacing between opposing parts of the coil conductor 25.

[0064] According to the above embodiment, the dielectric strength of the coil component 1 can be increased compared to conventional components. As a result, even if the spacing between opposing parts of the coil conductor 25 is designed to be smaller than the spacing between coil conductors in conventional coil components that do not contain ceramic particles, the same insulation resistance as the conventional coil component can be obtained. This makes it possible to reduce the size of the component.

[0065] Compared to information and communication devices such as smartphones, coil components used in automotive electrical systems are subjected not only to large currents but also to high voltages. Therefore, coil components used in automotive electrical systems sometimes require insulation more than twice as high as conventional coil components mainly used in information and communication devices. The coil component according to the above embodiment can also be used in applications requiring such high insulation.

[0066] The dimensions, materials, and arrangements of each component described herein are not limited to those explicitly described in the embodiments, and each component can be modified to have any dimensions, materials, and arrangements that may fall within the scope of the present invention. Furthermore, components not explicitly described herein may be added to the described embodiments, and some of the components described in each embodiment may be omitted.

[0067] The invention described in the original claims of the present application is listed below. [1] A substrate comprising metallic magnetic particles having a first average particle size and ceramic particles having a second average particle size smaller than the first average particle size, A coil conductor provided within the base body, including a first conductor portion and a second conductor portion provided within the base body so as to face the first conductor portion, Equipped with, In the interconductor region of the substrate between the first conductor portion and the second conductor portion, the volume ratio of the ceramic particles to the total volume of the metal magnetic particles and the ceramic particles is 3 vol% or more. Coil components. [2] The content ratio of the ceramic particles to the metal magnetic particles in the interconductor region is 15 vol% or less. The coil component described in [1]. [3] The first conductor portion and the second conductor portion are made of a conductive material containing metal, The substrate substantially does not contain atoms of the metal in the interconductor region. The coil component described in [1] or [2]. [4] The ceramic particles consist of silica, alumina, zirconia, or titania. A coil component as described in any of [1] to [3]. [5] The second average particle size is less than 1 / 50 of the first average particle size. A coil component as described in any of [1] through [4]. [6] The second average particle size is 1 / 200 or more of the first average particle size. The coil component described in [5]. [7] A circuit board comprising a coil component as described in any of [1] to [6]. [8] An electronic component comprising the circuit board described in [7]. [9] A step of preparing a molded body comprising metallic magnetic particles having a first average particle size and ceramic particles having a second average particle size smaller than the first average particle size, with a coil conductor arranged inside the molded body, A step of heating the molded body at a temperature lower than the melting temperature of the ceramic particles, Equipped with, The volume ratio of the ceramic particles to the total volume of the metallic magnetic particles and the ceramic particles is 3 vol% or more. A method for manufacturing coil components. [Explanation of Symbols]

[0068] 1. Coil component 10 Base 10X Interconductor region 21, 22 External electrode 25 Coil conductors 31 Metal magnetic particles 32 Ceramic particles C11~C16 Conductor Pattern

Claims

1. A substrate comprising metallic magnetic particles having a first average particle size and ceramic particles having a second average particle size smaller than the first average particle size, A coil conductor provided within the base body, including a first conductor portion and a second conductor portion provided within the base body so as to face the first conductor portion, Equipped with, The substrate has an interconductor region between the first conductor portion and the second conductor portion, The interconductor region includes the metallic magnetic particles and the ceramic particles, In the interconductor region, the volume ratio of the ceramic particles to the total volume of the metal magnetic particles and the ceramic particles is 3 vol% or more. The content of the metallic magnetic particles in regions of the substrate other than the interconductor region is greater than the content of the metallic magnetic particles in the interconductor region. Coil components.

2. The coil conductor has a conductor pattern that extends around the coil axis, The substrate has a core region located inward from the conductor pattern in the radial direction centered on the coil axis. The content of the metallic magnetic particles in the core region is greater than the content of the metallic magnetic particles in the interconductor region. The coil component according to claim 1.

3. The aforementioned metallic magnetic particles have a thin film containing silica on their surface. The coil component according to claim 1 or 2.

4. The thin film is made of silica. The coil component according to claim 3.

5. The ceramic particles consist of silica, alumina, zirconia, or titania. A coil component according to any one of claims 1 to 4.

6. The aforementioned metallic magnetic particles are bound together by a binder. A coil component according to any one of claims 1 to 5.

7. The aforementioned binder includes resin. The coil component according to claim 6.

8. The substrate does not have a visible boundary in the region excluding the interconductor region. A coil component according to any one of claims 1 to 7.

9. Withstand voltage of 2V / μm or higher, A coil component according to any one of claims 1 to 8.

10. The coil conductor contains metal atoms, The interconductor region contains substantially no metal atoms included in the coil conductor. A coil component according to any one of claims 1 to 9.

11. A circuit board comprising a coil component according to any one of claims 1 to 10.

12. An electronic component comprising the circuit board described in claim 11.

Citation Information

Patent Citations

  • Composite magnetic material, magnetic element and manufacturing method of them

    JP2002305108A

  • Multilayer inductor

    JP2017092431A

  • Coil component and manufacturing method thereof

    JP2017228768A

  • Powder magnetic core and magnetic element using the same

    WO2010103709A1